Guidelines of Writing A Scientific Research Article - El Hadi Babikir, Haydar (Gezira Journal of Health Sciences; Vol 4 No 2 (2008), 2008)
Scientific research is an attentive and systematic inquiry or investigation into a subject in order to discover or revise facts, theories, applications, etc. Qualitative research for instance is a field of inquiry that crosscuts disciplines and subject matters. The discipline investigates the why and how of decision making, not just what, where, when. Hence, smaller but focused samples are more often needed rather than large random samples. Scientific research in medicine articles provide a method for scientists to communicate with other scientists about the results of their research. 1 Therefore, one of the goals of a scientific research publication is to enables this communication. The research scientists, unlike other professions, must provide documents showing what he or she did, why it was done, how it was done and what was learned from it. This reproducibility makes science and scientific writing distinctive. 2,3 However; many good scientists are poor writers. Certainly, many scientists do not like to write. 4,5 The main purpose of this review is to share with others ideas about the appropriate way of writing their scientific works, to be accepted for publication; however, it is not possible to offer recommendations that are universally acceptable.